Akkermansia muciniphila and its culture supernatant ameliorate colitis in interleukin-10 knockout mice via gut barrier and immune modulation - Jiang, Mingshan; Jia, Yongbin; Ma, Chunxiang; Zeng, Zhen; Li, Yan; Li, Lili; Lin, Hao; Pang, Jiangmei; Li, Jiaxin; Chen, Jingjing; Li, Xi; Chen, Kexin; et al. (Frontiers in Immunology, 2025)
BackgroundAkkermansia muciniphila (A. muciniphila) is a mucin-degrading commensal bacterium with established roles in maintaining intestinal homeostasis and modulating host immune responses. However, its therapeutic potential and mechanisms in chronic spontaneous colitis remain incompletely defined. Interleukin-10 knockout (IL-10−/−) mice are a well-established model of spontaneous colitis due to impaired anti-inflammatory cytokine signaling and disrupted immune regulation. In this study, we aimed to determine whether A. muciniphila and its culture-derived supernatant could ameliorate intestinal inflammation in IL-10−/− mice.MethodsWe administered A. muciniphila or its culture supernatant (A. muciniphila supernatant [A.m-SN]) to IL-10−/− mice and monitored disease progression over 30 days. Clinical assessments included body weight, disease activity index (DAI), colon length, histopathology, and endoscopy. Tight junction proteins (zonula occludens-1 [ZO-1] and Occludin) and colonic messenger ribonucleic acid levels of pro- and anti-inflammatory cytokines were evaluated. Gut microbiota composition was assessed using 16S ribosomal deoxyribonucleic acid sequencing, and untargeted metabolomic profiling was performed on the culture medium to identify potential anti-inflammatory components.ResultsMice treated with A. muciniphila or A.m-SN showed significantly reduced colitis severity, including reduced body weight loss, lower DAI, preserved colon length, and improved histological scores. Immunofluorescence revealed increased expression of ZO-1 and Occludin in colonic tissues. Pro-inflammatory cytokines (tumor necrosis factor-α, IL-6, IL-17, IL-1β, and interferon-γ) were downregulated, while anti-inflammatory cytokines (IL-4, transforming growth factor-β, and IL-22) were upregulated in treated groups. Gut microbiota analysis showed partial restoration of microbial diversity and structure. Metabolomic profiling identified distinct signatures in A.m-SN, with bioactive molecules such as adenosine and tryptophan derivatives implicated in the anti-inflammatory effects.ConclusionThe culture supernatant of A. muciniphila alleviated spontaneous colitis in IL-10−/− mice by suppressing pro-inflammatory cytokines, enhancing anti-inflammatory mediators, and strengthening epithelial barrier function. Metabolomic profiling identified candidate bioactive components, including adenosine and tryptophan derivatives, supporting its potential as a postbiotic intervention for inflammatory bowel disease.